Resilience of Public Spheres in a Global Health Crisis - Trenz, Hans-Jörg; Heft, Annett; Vaughan, Michael; Pfetsch, Barbara (Javnost-The Public, 2021)
The Covid-19 pandemic disrupted “normal” modes of public sphere functioning and activated an experimental mode of coping, reinventing forms of publicness and communicative exchanges. We conceptualise the social responses triggered by the crisis as particular forms of public sphere resilience and assess the role of digitalisation and digital spaces in the emergence of distinct modes and dynamics of resilience. Four areas of enhanced public sphere experimentation are examined with respect to our conceptualisation: political consumerism, digital modes of solidarity, political protest mobilisation, and news consumption. We discuss overarching features of public sphere resilience across societal sub-spheres and highlight the dynamics and hybridities which structure the emerging public spaces. Resilience practices are accompanied by dynamics of politicisation and depoliticisation coupled with shifting boundaries of publicness and privateness. Our observations likewise reveal the dynamic interplay between resilience and resistance.